2019
DOI: 10.1186/s12888-019-2041-7
|View full text |Cite
|
Sign up to set email alerts
|

Daily variation in post traumatic stress symptoms in individuals with and without probable post traumatic stress disorder

Abstract: BackgroundLittle is known about the extent to which post traumatic stress symptoms (PTSS) vary from day to day in individuals with post traumatic stress disorder (PTSD). This study examined the variation of PTSS by day of the week, and whether daily or day of week variation differs between individuals with and without probable PTSD.MethodsSubjects (N = 80) were assessed for probable PTSD at enrollment. Using an ecological momentary assessment methodology, PTSS were assessed four times daily by self-report for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
(32 reference statements)
1
22
0
Order By: Relevance
“…Another reason to use and incorporate the PC-PTSD into suicide risk assessment strategies is that, unlike a medical records diagnosis, the PC-PTSD asks a patient about PTSD symptoms experienced within the past month. The symptom severity of PTSD may fluctuate daily, 25 and this fluctuation has been linked to adverse health outcomes. 44 Although further research is warranted, findings from the present analysis suggest that the PC-PTSD might be a better indicator of immediate suicide mortality risk than a static diagnosis obtained from the medical record.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason to use and incorporate the PC-PTSD into suicide risk assessment strategies is that, unlike a medical records diagnosis, the PC-PTSD asks a patient about PTSD symptoms experienced within the past month. The symptom severity of PTSD may fluctuate daily, 25 and this fluctuation has been linked to adverse health outcomes. 44 Although further research is warranted, findings from the present analysis suggest that the PC-PTSD might be a better indicator of immediate suicide mortality risk than a static diagnosis obtained from the medical record.…”
Section: Discussionmentioning
confidence: 99%
“…Future research may determine whether sleep characteristics have a greater impact on specific symptoms (e.g., hyperarousal symptoms) versus other symptoms. Some sleep characteristics such as sleep duration may vary during the week and it will be important to examine whether they influence the day of week variation in PTSS [32]. Finally, future studies should examine whether interventions for sleep disturbance can prevent the onset of PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Of the N = 141 who enrolled, n = 61 with probable PTSD were included in data analyses, n = 59 did not have PTSD, n = 12 did not return the daily assessments, n = 6 did not provide four or more daily assessments, n = 2 did not complete the assessment of probable PTSD, and n = 1 was removed as an outlier. This study was part of a larger data collection project looking at post traumatic stress in U.S. military personnel and methods common to the larger study can be found in a prior publication [32].…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations